Prescription drug cost sharing: associations with medication and medical utilization and spending and health - Goldman, Dana P. (JAMA, 2007)
CONTEXT: Prescription drugs are instrumental to managing and preventing chronic disease. Recent changes in cost-sharing could affect access to them. OBJECTIVE: To synthesize published evidence on the associations among cost-sharing features of prescription drug benefits and use of prescription drugs, use of nonpharmaceutical services, and health outcomes. DATA SOURCES: We searched PubMed for studies published in English between 1985 and 2006. STUDY SELECTION & DATA EXTRACTION: Among 923 articles found in the search, we identified 132 articles examining the associations between prescription drug plan cost-containment measures, including co-payments, tiering, or coinsurance (n = 65), pharmacy benefit caps or monthly prescription limits (n = 11), formulary restrictions (n = 41), and reference pricing (n = 16), and salient outcomes, including pharmacy utilization and spending, medical care utilization and spending, and health outcomes. DATA SYNTHESIS: Increased cost-sharing is associated with lower rates of drug treatment, worse compliance among existing users, and more frequent discontinuation of therapy. For each 10% increase in cost-sharing, prescription drug spending falls by 2% to 6%, depending on the class of drugs and the patient’s condition. The reduction in use associated with a benefit cap, which limits either the coverage amount or the number of covered prescriptions, is consistent with other cost-sharing features. For some chronic conditions, higher cost-sharing is associated with increased use of medical services, at least for patients with congestive heart failure, lipid disorders, diabetes, and schizophrenia. While low-income groups may be more sensitive to increased cost-sharing, there is little evidence to support this contention. CONCLUSIONS: Pharmacy benefit design represents an important public health tool for improving patient treatment and adherence. While increased cost-sharing is highly correlated with reductions in pharmacy use, the long-term consequences of benefit changes on health are still uncertain. guidance on conducting a systematic evidence review.